Detection of Fungi in Hair-brushes in Beauty Salons at Jatinangor - Susanna Mitchelle Edward; Imam Megantara; Reiva Farah Dwiyana (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Various beauty tools are used in beauty salons, among those is the hair-brush. The hair-brush can conceal various human skin pathogens although under harsh environmental conditions, most pathogens are killed; nevertheless, few microorganisms, such as the fungi can adapt and survive. Moreover, the moist conditions of the hair-brush predisposes the growth of fungi however the ability of these fungi to instigate disease in an individual is dependent on the portal of entry and the host immunological status. This study was conducted to determine the fungus that is present in the beauty salon’s hair-brushes.Methods: This study was conducted in beauty salons located in Jatinangor area during September–October 2013 using the descriptive laboratory method. Fifteen beauty salons were included in this study based on sample size calculation for dichotomous variable. The specimens from all the hair-brushes were collected after the owner’s informed consent, then cultured onto 30 sabouraud agar, two for each beauty salon (dermatophyte and non-dermatophyte agar). The fungi were detected macroscopically and microscopically.Results: Overall, 93% revealed to be culture positive, with 90% of them were found to be non-dermatophytes, most of which are saprophytic fungi. The remaining 3% were dermatophytes.Conclusions: Beauty salon’s hair-brushes contain a wide range of fungi distribution which may be a source of fungal colonization. However, most of the fungi found in the beauty salons are saprophytic fungi, therefore it is unnecessary to be anxious about a small amount of pathogenic fungi are found in humans. [AMJ.2015;2(4):516–20] DOI: 10.15850/amj.v2n4.636